Molecular basis of oxidative stress : chemistry, mechanisms, and disease pathogenesis - Villamena, Frederick A. (Hoboken, New Jersey : Wiley, 2013)
Focusing on the molecular and chemical bases of oxidative stress, which can cause cancer as well as cardiovascular and neurodegenerative diseases, Molecular Basis of Oxidate Stress discusses the role of free radicals in disease, diagnosis, and therapeutics. Written by recognized leaders in the field, the book provides in-depth knowledge about the mechanisms of oxidative stress and damage, free radical chemistry, and the role of free radicals in disease, diagnosis, and therapeutics.
""Concluding Remarks""""9: Oxidative Stress and Redox Signaling in Carcinogenesis""; ""Overview""; ""9.1 Redox Environment and Cancer""; ""9.2 Oxidative Modifications to Biomolecules and Carcinogenesis""; ""9.3 Measurement of Oxidative DNA Damage in Human Cancer""; ""9.4 Epigenetic Involvement in Oxidative Stress-Induced Carcinogenesis""; ""9.5 Deregulation of Cell Death Pathways by Oxidative Stress in Cancer Progression""; ""Conclusions and Perspective""; ""Acknowledgments""; ""10: Neurodegeneration from Drugs and Aging-Derived Free Radicals""; ""Overview""; ""10.1 ROS Formation""
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Oxidative stress; Oxidation; Oxidative stress; SCIENCE -- Life Sciences -- Anatomy & Physiology; Oxidation; Oxidative stress; Electronic books; Electronic books